LIVED ACADEMIC AND SPIRITUAL LIFE EXPERIENCES THROUGH SONGS OF THEOLOGY STUDENTS - Anne Lou M. Hendriks (Jurnal Koinonia, 2019)
Songs are believed to contribute to the success of students not only in their academiclife (Alisaari & Heikkola, 2016; Ashtiani & Zafarghani, 2015; & Rafiee, Kassaian,& Dastjerdi, 2010) but spiritual life (White, 2014) as well. The purpose of this studywas to examine the lived academic and spiritual life experiences through songs oftheology students. This phenomenological study, with 35 theology students from aprivate university in West Indonesia as participants, generated four themes whichinclude God’s presence, God’s love, self-disposition, and positive learning. It istherefore recommended that tertiary teachers employ spiritual-uplifting songs for theenhancement of both academic and spiritual life aspects of the learners